The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1097/sla.0000000000001448
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Depression on Recovery After Major Noncardiac Surgery

Abstract: Nearly 1 quarter of patients undergoing major abdominal surgery are depressed preoperatively. This depression is a strong independent predictor of prolonged LOS and partly explains surgeons' failure to predict outcome accurately.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 47 publications
(38 reference statements)
0
20
1
Order By: Relevance
“…In order to test the hypothesis that improved FC is associated with a reduction of the severity of complications after surgery, the CCI is presented both as a continuous and a dichotomous variable, using upper quartile as the cutoff for defining major/severe complication, as described in the literature [26]. Association between gain in the 6MWD and 30 d post-surgical severe complications were tested using logistic regression, and univariable and multivariable logistic regression are presented.…”
Section: Discussionmentioning
confidence: 99%
“…In order to test the hypothesis that improved FC is associated with a reduction of the severity of complications after surgery, the CCI is presented both as a continuous and a dichotomous variable, using upper quartile as the cutoff for defining major/severe complication, as described in the literature [26]. Association between gain in the 6MWD and 30 d post-surgical severe complications were tested using logistic regression, and univariable and multivariable logistic regression are presented.…”
Section: Discussionmentioning
confidence: 99%
“…68 These trials showed a greater ability to detect differences between treatment effects than classic endpoints such as 'any complication' or 'major complication' defined according to the Clavien-Dindo classification. The index has been used in large multi-centric studies, [69][70][71][72][73][74][75][76][77] notably as a benchmark endpoint for major surgery. 70 Exploring the potential added value of the comprehensive comprehensive index to standard assessment of postoperative morbidity, and to clarify potential controversies for its application, Clavien et al 78 reported that it yielded substantial additional value to the Clavien-Dindo classification in patients with more than one complication.…”
Section: Descriptionmentioning
confidence: 99%
“…This implies that the use of the CCI 1 may significantly decrease the sample sizes in future studies. 7 The CCI 1 has been used in large multicentric studies, [9][10][11][12][13][14][15][16][17] as a benchmark endpoint for major surgery, 10 or in individual centers to assess quality and individual surgeon's performance (Han-Kwang Yang, ASA 2016, personal communication).…”
Section: Learning Objectivesmentioning
confidence: 99%